The Black Ocean - Barker, Brian, 1973- (Book collections on Project MUSE., 2011)
In The Black Ocean, poet Brian Barker attempts to make sense of some of the darkest chapters in history while peering forward to what lies ahead as the world totters in the wake of human complacence. Unveiled here are ruminations on human torture, the Chernobyl disaster, the aftermath of Hurricane Katrina, and genocide against Native Americans. The ghosts of Lincoln, Poe, and Billie Holiday manifest from pages laden with grim prophecies and catastrophes both real and imagined. These hauntingly intense documentary poems reflect on the past in an attempt to approach it with more.